Examining the Role of Village Officials in Land Mafia Crimes (Case Study: Land Plot Sale and Purchase in Sidokerto Village, Buduran District, Sidoarjo Regency) - Sitompul, Herman; Fitriyanti, Fitriyanti; Rizki Aji Putra, Gilang (UIN Jakarta, 2025)
This study examines the legal relationship between village government and land affairs, as well as the involvement of village officials in land mafia crimes. As the lowest administrative unit, villages hold the authority to issue land documents such as Land Ownership Certificates (SKT), which play a crucial role in the land registration process. However, this authority is often misused by corrupt officials who manipulate documents to serve the interests of land mafias. A case study conducted in Sidokerto Village reveals that illegally issued SKTs are used to legitimize unlawful land transactions. This research adopts a socio-legal (empirical) method with a case study approach. It considers law as both a normative system and a social reality. Primary data were obtained through in-depth interviews with affected residents, village officials, notaries/PPAT, land office (BPN) personnel, and police officers, as well as field observation and legal document analysis. The data were analyzed qualitatively to interpret the gap between legal norms and their implementation, and to uncover patterns of land-related crimes involving village actors. The findings underscore the urgency of stricter oversight, digitalization of land administration at the village level, and policy reform to prevent abuse of authority. Keywords: Village, land affairs, Land Ownership Certificate, land mafia, socio-legal research